2012
DOI: 10.1248/bpb.35.449
|View full text |Cite
|
Sign up to set email alerts
|

<i>Astragalus</i> Extract Alleviates Nerve Injury after Cerebral Ischemia by Improving Energy Metabolism and Inhibiting Apoptosis

Abstract: This aim of this study was to explore the effects and molecular mechanisms of Astragalus extract against cerebral ischemia injury through the energy metabolism and apoptosis pathways of c-Jun N-terminal kinase (JNK) signal transduction. After the bilateral common carotid artery of C57BL/6 mice was occluded for 20 min followed by 1-h reperfusion, the ATP content, total adenine nucleotides (TAN), energy charge (EC), and sodium potassium ATPase (Na -K -ATPase) activity were decreased markedly in brain tissues. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 18 publications
3
22
0
2
Order By: Relevance
“…The result revealed a significant increase in ATP content in TNBS-injured rats when subjected to HQJZ treatment, suggesting the capacity of HQJZ to increase the energy supply, consistent with the result from others [31]. Energy metabolism is a process involving multiple reactions coordinated by numerous proteins, among which ATP synthase plays a central role, while AMPK acts as an energy sensor to monitor the energy status of the cell [46].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The result revealed a significant increase in ATP content in TNBS-injured rats when subjected to HQJZ treatment, suggesting the capacity of HQJZ to increase the energy supply, consistent with the result from others [31]. Energy metabolism is a process involving multiple reactions coordinated by numerous proteins, among which ATP synthase plays a central role, while AMPK acts as an energy sensor to monitor the energy status of the cell [46].…”
Section: Discussionsupporting
confidence: 76%
“…These results support the application of HQJZ in IBD [30]. Furthermore, study showed that Astragalus (one of main components of HQJZ) extract increases the levels of ATP and ADP and the activity of Na(+)-K(+)-ATPase, improves energy metabolism, and inhibits apoptosis, alleviating neuron injury after cerebral ischemia [31]. We speculated that HQJZ may be beneficial for IBD by acting at multiple targets involving regulation of energy metabolism.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Energy metabolism includes anabolism and catabolism, involving many biological enzymes [27]. Na + -K + -ATPase and Ca 2+ -Mg 2+ -ATPase are the two main ATP degradation enzymes, which can hydrolyze ATP to supply direct free energy [28]. It plays an important role in maintaining the physiologic functions of material transport, energy conversion, and information transmission [29].…”
Section: Discussionmentioning
confidence: 99%
“…The energy‐rich phosphate compound synthesis was significantly reduced after cerebral ischemia. Astragalus extract, AS‐IV (20–40 mg/kg, 3–7 day) alone or in combination with tetramethylpyrazine, could reverse the decreased glucose metabolism, increase the ATP and ADP level, the Na+‐K+‐ATPase activity, and the EC value, and improve the energy synthesis and supply to attenuate cerebral ischemia damage .…”
Section: Pharmacological Effect Of Astragaloside IVmentioning
confidence: 99%